DEVELOPMENT OF AUDIO-VISUAL MEDIA IN LISTENING LEARNING FOR GRADE IV ELEMENTARY SCHOOL STUDENTS - Nadya Putri Pradina; Eva Astuti Mulyani (Education Generation Journal, 2022)
This study aims to produce an audio-visual learning media product that is useful in listening learning for fourth grade elementary school students. And to determine the feasibility of the audio-visual media that the researchers have developed. This study uses the Research and Development (R&D) method and using the Four-D model research stage (Define, Design, Develop, Disseminate). Validation is carried out by expert validators and practitioner validators. Product trials were carried out in stages, namely stage 1 and stage 2. The results showed that the validation of design experts obtained an assessment with a very valid category. In validation linguists obtained assessment with a very valid category. In the validation of the material experts, they obtained an assessment with a very valid category. And the validation of the material by the practitioner validator obtained an assessment with a very valid category. The students written test in the form of objective questions received an assessment with a very good category. The results of the questionnaire responses from students and teachers obtained an assessment with a very practical category. So, the results of this study indicate that development of audio-visual media in listening learning is very suitable for use for fourth grade elementary school students.